Power Electronics for the Next Generation Wind Turbine System - Ma, Ke.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book presents recent studies on the power electronics used for the next generation wind turbine system. Some criteria and tools for evaluating and improving the critical performances of the wind power converters have been proposed and established. The book addresses some emerging problems as well as possibilities for the wind power conversion, and may be useful as an inspiring reference for the researchers in this field.
Keywords: Renewable energy resources; Power electronics; Renewable and Green Energy; Renewable and Green Energy; Power Electronics, Electrical Machines and Networks